The World Bank Group Partnership with the Philippines, 2009–18 : Country Program Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2020)
This Country Program Evaluation (CPE) assesses the development effectiveness of the World Bank Group program in the Philippines between 2009 and 2018. The report provides input to the next Country Partnership Framework for the Philippines and may offer lessons for Bank Group country programs in other lower-middle-income countries facing similar development challenges.